Pengelolaan Sumberdaya Manusia Dalam Peningkatan Kapabilitas Aparat Pengawasan Intern Pemerintah di Pemerintah Kabupaten Mahakam Ulu - Hendra Wibowo Hului; Bambang Irawan; Rita Kalalinggi (Department of Accounting, Faculty of Economics & Business, 2023)
The purpose of this study is to describe and analyze how resource management is to increase the capability of the Government Internal Supervisory Apparatus (APIP) in the Mahakam Ulu District Government. This study used a qualitative descriptive approach, using primary data, and secondary data, which were analyzed through an interactive model. This study concludes that the management of human resources in increasing the capability of the Government Internal Supervisory Apparatus (APIP) in the Mahakam Ulu Regency Government, in general, has been carried out well but not optimal, it can be seen that competence development has been carried out through Training, Bimtek, Seminars, Webinars and supported by adequate funding. Likewise, the provision of incentives is carried out through TPP, as stated in Perbub No. Perbub 23 of 2021 with varying amounts according to the level of position. Then a conducive work environment and leadership elements have developed a strategy by building teamwork, starting with good coordination before carrying out supervision in the field. Furthermore, the human resource procurement process has been carried out through the 2019 CPNS procurement and inpassing process. However, this number has yet to reach the ideal number under the existing workload and inadequate work support facilities and tools.